Adaptive Water Resource Planning in the South Saskatchewan River Basin: Use of Scenarios of Hydroclimatic Variability and Extremes1. (6th January 2016) - Sauchyn, David J.; St‐Jacques, Jeannine‐Marie; Barrow, Elaine; Nemeth, Michael W.; MacDonald, Ryan J.; Sheer, A. Michael S.; Sheer, Daniel P.
Abstract: The South Saskatchewan River Basin is one of Canada's most threatened watersheds, with water supplies in most subbasins over‐allocated. In 2013, stakeholders representing irrigation districts, the environment, and municipalities collaborated with researchers and consultants to explore opportunities to improve the resiliency of the management of the Oldman and South Saskatchewan River subbasins. Streamflow scenarios for 2025‐2054 were constructed by the novel approach of regressing historical river flows against indices of large‐scale ocean‐atmosphere climate oscillations to derive statistical streamflow models, which were then run using projected climate indices from global climate models. The impacts of some of the most extreme scenarios were simulated using the hydrologic mass‐balance model Operational Analysis and Simulation of Integrated Systems (OASIS). Based on stakeholder observations, the project participants proposed and evaluated potential risk management and adaption strategies, e.g., modifying existing infrastructure, building new infrastructure, changing operations to supplement environmental flows, reducing demand, and sharing supply. The OASIS model was applied interactively at live modeling sessions with stakeholders to explore practical adaptation strategies. Our results, which serve as recommendations for policy makers, showed that forecast‐based rationing together with new expanded storage could dramatically reduce water shortages.